The Influence of Market Orientation and Product Innovation on the Marketing Performance of Fashion SMEs in South Tangerang City - Kencana, Putri Nilam; Diposumarto, Ngadino Surip; Farradia, Yuary (Formosa Journal of Science and Technology, 2025)
The purpose of this study is to investigate how product innovation and market orientation affect the marketing performance of fashion SMEs in South Tangerang City. The research employed an associative methodology, with a population comprising 112 fashion SMEs in the area. Data analysis methods included correlation coefficients, coefficients of determination, partial t-tests, simultaneous F-tests, simple linear regression, and multiple linear regression. The findings demonstrate that market orientation significantly and favorably affects marketing performance, as shown by the basic linear regression equation.Y = 23.735 + 0.422X. The correlation coefficient is 0.868 (very strong), with a determination coefficient of 75.4%. Furthermore, t-value (tcount) is 18.357, exceeding the t-table value of 1.981 with a significance level of 0.000 (<0.05). Similarly, product innovation has a positive and significant effect on marketing performance, demonstrated by the equation Y = 23.272 + 0.434X. The correlation coefficient is 0.769 (strong), and the determination coefficient is 59.1%. The t-value (tcount) is 12.619, greater than the t-table value of 1.981 with a significance level of 0.000 (<0.05). Simultaneously, market orientation and product innovation together positively and significantly affect marketing performance, supported by the multiple linear regression equation Y = 22.535 + 0.345X1 + 0.111X2. The correlation coefficient is 0.876 (very strong), with a determination coefficient of 76.7%. The F-value (Fcount) is 179.885, exceeding the F-table value of 3.93 with a significance level of 0.000 (<0.05).